Type D Personality, Stress Level, Life Satisfaction, and Alcohol Dependence in Older Men - Bejda, Grzegorz; Kułak-Bejda, Agnieszka; Waszkiewicz, Napoleon; Krajewska-Kułak, Elzbieta (Frontiers in Psychiatry, 2021)
Alcohol consumption among the elderly is becoming an increasing public health problem due to the rapidly growing elderly population. There is a theory that Type D personality was significantly and positively correlated with alcohol dependence. The aim of the study was the assessment of the style of coping with stress, emotions, and anxiety in elder men addicted to alcohol and the relationship between the above. The study included 170 men addicted to alcohol aged 60 years and older (mean age - 63 ± 3.1 years) staying in the Department of Alcohol Addiction Therapy for Men. They were tested with the questionnaire sheet and the following scales: Perceived Family Wealth (PFW), Familly Fluence Scale (FAS), Cantril's Ladder of Life Scale, The Satisfaction with Life Scale, the Type D Personality Scale-14 (DS14) and The 10-item Perceived Stress Scale (PSS-10). The respondents' wealth on a scale of 1-5 points. assessed on avg. 3.1 ± 0.2. The above was confirmed by the results of the FAS scale study, where the respondents obtained an average of 3.9 ± 1.9 (min. 1, max. 8), which proves their average level of affluence. Assessment of the satisfaction with life using the Catril Ladder showed that the respondents were also satisfied with life on average (on average 5.5 ± 1.9). The assessment of life satisfaction using the SWLS scale allowed for the conclusion that the respondents were very dissatisfied with their lives (mean 17.2 ± 4.9). The assessment of the measurement of perceived stress (PSS-10 scale) showed that the respondents obtained an average of 23.5 ± 3.7 and on the sten scale, mean 7.7 ± 0.98 which proves a high level of perceived stress. The study using the DS14 scale showed that the respondents obtained in the NE subscale - 17.4 ± 4.5 points, and in the HS scale - 16.2 ± 3.2, which proves that they can be classified as a D personality. The participants were very dissatisfied with their lives, with a high level of perceived stress and D personality.